Literacy, Numeracy and Activation among the Unemployed - KELLY, ELISH MARY; MC GUINNESS, SEAMUS; O'CONNELL, PHILIP J. (ESRI)
Literacy and numeracy are key factors shaping individual life chances and their impact is particularly critical in the labour market. Large-scale sweeping changes in the organisation of work, including the shift from manufacturing to services and the spread of information technology in the knowledge economy, have progressively increased the importance of basic skills, including literacy and numeracy. The recent unemployment crisis in Ireland is likely to have exacerbated this long-run trend by increasing the competition for scarce jobs. It is well known that individuals with literacy and numeracy difficulties are more likely to be unemployed (see, for example, Robinson, 1998; Bynner, 2004; and Parsons and Bynner, 2007). Furthermore, in the course of the development of a national profiling system to identify individuals at risk of becoming long-term unemployed, research by the Economic and Social Research Institute (ESRI) found that literacy and numeracy difficulties were critical factors that increased the likelihood of long-term unemployment (O?Connell, McGuinness, Kelly and Walsh, 2009). Given this, it should follow that basic literacy and numeracy skill development should be a key component of any country?s labour market policy, and in particular policies associated with unemployment. Apart from the O?Connell et al. (2009) research, very little is known about the experiences of unemployed individuals with literacy and/or numeracy difficulties in Ireland. Specifically, we lack evidence on the assistance that such individuals receive through the National Employment Action Plan (NEAP), which is Ireland?s main activation policy for assisting those that are unemployed to reintegrate back into the labour market. This study uses data from the DSP/ESRI Profiling Project, which is described below, and builds on the earlier ESRI research to address four questions related specifically to unemployed individuals with literacy and/or numeracy difficulties: 1. What effect does age, educational attainment, health status and geographic location have on a newly registered unemployed person?s likelihood of having a literacy and/or numeracy difficulty? 2. What impact does literacy and/or numeracy difficulties have on an unemployed individual?s likelihood of exiting unemployment to employment within 12 months? Preventing people from falling into long-term unemployment (LTU) is a key objective of policymakers because of the negative implications that it has for both the individual (e.g. deskilling, scarring, poverty, etc.) and society as a whole (e.g. social welfare costs, lost revenue, crime, etc.). 3. What effect does having a literacy and/or numeracy difficulty have on the likelihood of an individual accessing government-sponsored training programmes? Specifically, what are the types of labour market programmes to which individuals with numeracy and/or literacy difficulties are generally assigned? 4. Finally, what is the relative effectiveness of labour market training among claimants reporting literacy and/or numeracy difficulties in achieving successful exits from the Live Register?
PUBLISHED
Keywords: NALA; National Adult Literacy Agency; Literacy